The Efficacy of Public Education as a Means of Social Mobility for the Indigenous Tribal Populations of Rural India. (July 2016) - Mukherjee, Anirban; Goe, W. Richard; Middendorf, Gerad
India is home to a diverse number of indigenous tribal groups collectively known as the 'adivasis'. As part of a tribal development strategy, the Indian government extended the public school system to serve rural tribal areas. This qualitative study explores the efficacy of the rural school system as a means of promoting social mobility among the Santal, Birhor, Kharia, and Lodha tribes located in the state of West Bengal, India. The findings indicate that rural schools have poor facilities, lack resources, and offer environments that are not conducive to academic success by the majority of tribal students. The research also reveals how the challenges faced by tribal children in rural schools are exacerbated because of a lack of cultural competency on the part of education professionals who design and deliver the curriculum. Thus the schools largely fail in preparing tribal students for even the bottom rungs of the Indian labour market.